The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11250-013-0499-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Cryptosporidium spp. infections in water buffaloes from northeast Thailand

Abstract: The objectives of this study were to determine the individual and herd-level prevalence and genotype of Cryptosporidium and to identify putative risk factors associated with Cryptosporidium spp. infections in water buffaloes in northeast Thailand. Fecal samples from 600 water buffaloes of 287 farms in six provinces were collected and tested using DMSO-modified acid-fast staining and polymerase chain reaction. The overall prevalence of Cryptosporidium infections in buffaloes was 5.7 and 8.7% among individual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
0
14
4
Order By: Relevance
“…parvum was the predominant species in young buffaloes (Cacciò et al 2007;Maurya et al 2013;Inpankaew et al 2014), and in the previous study in Australia, C. parvum was only detected in buffalo <6 months of age (Abeywardena et al 2013a). In the present study, however, all buffalo samples were adults (2-5 years), indicating that this species can also commonly infect adult buffaloes.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…parvum was the predominant species in young buffaloes (Cacciò et al 2007;Maurya et al 2013;Inpankaew et al 2014), and in the previous study in Australia, C. parvum was only detected in buffalo <6 months of age (Abeywardena et al 2013a). In the present study, however, all buffalo samples were adults (2-5 years), indicating that this species can also commonly infect adult buffaloes.…”
Section: Discussioncontrasting
confidence: 60%
“…This species has been detected previously in buffaloes in many countries including Spain, Italy, Australia, Egypt, India, and Thailand (Amer et al 2013;Cacciò et al 2007;Gómez-Couso et al 2005;Maurya et al 2013;Abeywardena et al 2013a;Inpankaew et al 2014;Mahfouz et al 2014;Aquino et al 015). Previous studies have reported that C.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…() in Egypt and Inpankaew et al. () in Thailand. Together with these publications, our study confirms that C. ryanae infects other ruminants than cattle, and is likely to infect buffaloes worldwide.…”
Section: Discussionmentioning
confidence: 98%